Effects of biological sex and pregnancy in experimental autoimmune encephalomyelitis: It’s complicated - McCombe, Pamela A.; Greer, Judith M. (Frontiers in Immunology, 2022)
Experimental autoimmune encephalomyelitis (EAE) can be induced in many animal strains by inoculation with central nervous system antigens and adjuvant or by the passive transfer of lymphocytes reactive with these antigens and is widely used as an animal model for multiple sclerosis (MS). There are reports that female sex and pregnancy affect EAE. Here we review the effects of biological sex- and pregnancy-related changes in susceptibility, clinical course, and pathophysiology of EAE. We also review reports of the possible mechanisms underlying these differences. These include sex-related differences in the immune system and in the central nervous system, effects of hormones and the sex chromosomes and a variety of molecules unique to pregnancy, and other intrinsic and extrinsic factors that can modify the course of EAE but that can also be affected by biological sex. Our conclusion from these reports is that the effects of sex vary from one animal model to another and are complex and cannot be widely extrapolated. In EAE, it is therefore essential that studies looking at the effects of biological sex or pregnancy give full information about the model that is used (i.e. animal strain, sex, the inducing antigen, timing of EAE induction in relation to pregnancy etc). In addition, it would be preferable if more than one EAE model were used, to show if any observed effects are generalizable. This is clearly a field that requires further work. However, understanding of the mechanisms of sex differences could lead to greater understanding of EAE, and suggest possible therapies for MS.